National and subnational burden of under-5, infant, and neonatal mortality in Ethiopia, 1990-2019: Findings from the Global Burden of Disease Study 2019. - Gizachew A Tessema; Tezera Moshago Berheto; Gavin Pereira; Awoke Misganaw; Yohannes Kinfu; GBD 2019 Ethiopia Child Mortality Collaborators (PLOS Global Public Health, 2023)
The under-5 mortality rate is a commonly used indicator of population health and socioeconomic status worldwide. However, as in most low- and middle-income countries settings, deaths among children under-5 and in any age group in Ethiopia remain underreported and fragmented. We aimed to systematically estimate neonatal, infant, and under-5 mortality trends, identify underlying causes, and make subnational (regional and chartered cities) comparisons between 1990 and 2019. We used the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD 2019) to estimate three key under-5 mortality indicators-the probability of death between the date of birth and 28 days (neonatal mortality rate, NMR), the date of birth and 1 year (infant mortality rate, IMR), and the date of birth and 5 years (under-5 mortality rate, U5MR). The causes of death by age groups, sex, and year were estimated using Cause of Death Ensemble modelling (CODEm). Specifically, this involved a multi-stage process that includes a non-linear mixed-effects model, source bias correction, spatiotemporal smoothing, and a Gaussian process regression to synthesise mortality estimates by age, sex, location, and year. In 2019, an estimated 190,173 (95% uncertainty interval 149,789-242,575) under-5 deaths occurred in Ethiopia. Nearly three-quarters (74%) of under-5 deaths in 2019 were within the first year of life, and over half (52%) in the first 28 days. The overall U5MR, IMR, and NMR in the country were estimated to be 52.4 (44.7-62.4), 41.5 (35.2-50.0), and 26.6 (22.6-31.5) deaths per 1000 livebirths, respectively, with substantial variations between administrative regions. Over three-quarters of under-5 deaths in 2019 were due to five leading causes, namely neonatal disorders (40.7%), diarrhoeal diseases (13.2%), lower respiratory infections (10.3%), congenital birth defects (7.0%), and malaria (6.0%). During the same period, neonatal disorders alone accounted for about 76.4% (70.2-79.6) of neonatal and 54.7% (51.9-57.2) of infant deaths in Ethiopia. While all regional states in Ethiopia have experienced a decline in under-5, infant, and neonatal mortality rates in the past three decades, the rate of change was not large enough to meet the targets of the Sustainable Development Goals (SDGs). Inter-regional disparities in under 5 mortality also remain significant, with the biggest differences being in the neonatal period. A concerted effort is required to improve neonatal survival and lessen regional disparity, which may require strengthening essential obstetric and neonatal care services, among others. Our study also highlights the urgent need for primary studies to improve the accuracy of regional estimates in Ethiopia, particularly in pastoralist regions.